Does the Method and Timing of Intravenous Ketamine Administration Affect Postoperative Morphine Requirement After Major Abdominal Surgery? - (:unkn) unknown (My University, 2014)
OBJECTIVE: Single intravenous bolus administration and postoperative or perioperative infusions are the most preferred methods of ketamine. Nevertheless, there is no clear explanation on the ideal ketamine administration method. In this study, we aimed to compare the effects of the most common ketamine administration methods and administration time on postoperative opioid consumption. METHODS: Fifty-two patients undergoing colectomy for colon cancer were randomly assigned into four groups. Group 1 was the control group. Group 2 received only a single intravenous bolus dose of 0.5 mg kg(-1) ketamine at induction. Group 3 received 0.5 mg kg(-1) intravenous ketamine bolus at induction and perioperative ketamine infusion at a rate of 0.25 mg kg(-1) h(-1). Group 4 received a bolus of 0.5 mg kg(-1) intravenous ketamine at induction and perioperative and postoperative ketamine infusion at a rate of 0.25 mg kg(-1) h(-1). Postoperatively, visual analogue scale pain scores, side effects, and morphine consumption were recorded. RESULTS: There was no statistically significant difference in postoperative pain scores. Total morphine consumption was found to be significantly lower in Group 4 compared to the other groups (p=0.03, p=0.004, p=0.03, respectively). During the 1(st), 2(nd), and 4(th) hours in the postoperative period, patient-controlled analgesia morphine consumption was significantly lower in Group 4 compared to the control group (p<0.01). CONCLUSION: Preoperative single-bolus dose or intraoperative low-dose ketamine infusion does not decrease postoperative morphine consumption; however, per- and postoperative 48-hour ketamine infusion has a significant effect in decreasing morphine consumption without decreasing the incidence of side effects in patients undergoing major abdominal surgery.
Keywords: Ketamine; colectomy; morphine; postoperative analgesia